Analysis of Coffee Raw Material Inventory Control Using the EOQ (Economic Order Quantity) Method in SME Sido Luhur - Sukosyah, Ananda Windi; Djoko Koestiono; Heptari Elita Dewi; Kiara Namira Rusli (HABITAT, 2023)
SME Sido Luhur is a producer that processes raw coffee beans who have problems ordering coffee beans every month which is considered to result in higher inventory costs. The sample in this study were SME Sido Luhur owner who were determined based on judgment sampling. The research was conducted at SME Sido Luhur starting September 2022. This research used primary data obtained through interviews and secondary data obtained from the cost and quantity of raw materials in 2018. Data for 2018 can represent 2019, 2020, 2021, 2022, and so on, because starting in 2017 SME Sido Luhur have entmered the maturity phase so the 2018 data can represent the following year based on the relatively stable use of raw materials and having entered the business maturity phase. The analysis method uses EOQ to find the optimum inventory quantity with the lowest possible cost and the right reorder time. A comparison of robusta coffee bean inventory control methods shows that the Economic Order Quantity method is more effective in controlling raw material inventory in SME Sido Luhur as evidenced by the cost of raw material inventory being economical and efficient. After using the EOQ method, orders are made every 2 months to save costs for ordering raw materials compared to before using the EOQ method, which is done every month.